2006
DOI: 10.1093/jn/136.12.2970
|View full text |Cite
|
Sign up to set email alerts
|

Chili, but Not Turmeric, Inhibits Iron Absorption in Young Women from an Iron-Fortified Composite Meal

Abstract: Chili and turmeric are common spices in indigenous diets in tropical regions. Being rich in phenolic compounds, they would be expected to bind iron (Fe)(3) in the intestine and inhibit Fe absorption in humans. Three experiments were conducted in healthy young women (n = 10/study) to assess the effect of chili and turmeric on Fe absorption from a rice-based meal containing vegetables and iron fortified fish sauce in vivo. Iron absorption was determined by erythrocyte incorporation of stable isotope labels ((57)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…They all received the same iron isotope-labeled reference meal. Sixtyseven participated in studies of iron-fortified fish sauce 29 and the effect of spices on iron absorption, 30 and 25 were healthy controls in a study of the effects of hemoglobinopathies on iron absorption (M Zimmermann, unpublished data). The first two studies have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They all received the same iron isotope-labeled reference meal. Sixtyseven participated in studies of iron-fortified fish sauce 29 and the effect of spices on iron absorption, 30 and 25 were healthy controls in a study of the effects of hemoglobinopathies on iron absorption (M Zimmermann, unpublished data). The first two studies have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…The first two studies have been reported previously. 29,30 Exclusion criteria included pregnancy, lactation, gastrointestinal disorders or metabolic diseases. The absence of thalassemia was verified by hemoglobin typing using a commercial HPLC-based autoanalyzer (Variant, Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…74 Chilli powder (Capsicum annuum) has been found to lower iron absorption in the GIT in humans 75 and the polyphenolic compounds in the spice (capsaicin) presumably causes this by forming complexes with iron within the gut. 76 The high mineral content of dandelion (Taraxacum officinale) is believed to result in the formation of complexes between drugs, resulting in a decreased absorption.…”
Section: Interactions Affecting Drug Absorptionmentioning
confidence: 99%
“…Awareness should also be made with the concurrent intake of certain fortified foods. Tuntipopipat et al (2006) reported a reduction in the absorption of iron by a group of healthy females that consumed iron-fortified foods together with Chilli pepper. The iron was bound to capsaicin, the polyphenos that are found in Chilli (Capsicum annum).…”
Section: Possible Therapeutic Failure or Development Of Drug Resistancementioning
confidence: 99%